Effect on mental health of health-care providers during COVID-19 pandemic - Arvind Sharma; Priyanka Dubey; Deepali Soni; Richa Sharma; Aditi Bharti; Tej Pratap Singh (Wolters Kluwer Medknow Publications, 2021)
Background: Health-care providers played a crucial role in responding to the public health emergency due to COVID-19 pandemic. Therefore, our study aimed to assess depression, anxiety, and stress (DAS) levels among the health-care providers in a COVID-19 dedicated health-care facility. Methodology: From the month of August to December 2020, a cross-sectional study was conducted on health-care providers who were involved in providing health-care services to COVID-19 patients in a tertiary care institute of Jabalpur by purposive convenient sampling through online Google Forms. The study tool used was validated depression, anxiety, and stress scale-21 having a good internal consistency having Cronbach's alpha value 0.85. Results: From 112 health-care providers, higher level of anxiety was found (29.46%) followed by depression (17.85%) and stress (16.07%). Mild, moderate, severe, and extremely severe anxiety were found in 18.75%, 7.14%, 1.78%, and 1.78%, respectively. Mild and moderate depression were found in 9.82% and 8.03%. Mild, moderate, and severe stress were found in 8.92%, 6.25%, and 0.89% of health-care providers, respectively. A significant association of depression, stress, and anxiety with designation of the participants was found (P < 0.001). Conclusion: To combat DAS, it is necessary to cascade awareness and knowledge should be disseminated. Regular screening of health-care providers, counseling, and stress management programs should be conducted.